Investigation of Students' Perception of Social Studies Education for Effective Citizenship in Federal College of Education, Pankshin, Nigeria - Irmiya, Ruth A.; Bitrus, Gamkur; Irmiya, Solomon Reuben (NIU Journal of Social Sciences, 2019)
The introduction of social studies as a school programme was basically meant to solve problems of man arising from his daily interaction with the environment.  This would in turn enable him to acquire basic skills, competences and effective citizen.  However the views held by different people about the discipline over the years has declined the realization of this object.  The purpose of this study is to investigate studentsâ€™ perception of Social Studies Education with bearings on effective citizenship in Federal College of Education Pankshin in Plateau State.  The cross-sectional survey research design is adopted to answer the research questions and four (4) hypotheses raised in the study.  The stratified sampling technique is used to select a sample size of 253 students from the population of 265 students.  28 items were drawn in a questionnaire which was later subjected to descriptive and inferential statistics for data analysis.  The mean and standard deviation are used for the research questions while the Pearson moment correlation was adopted in analyzing hypothesis one and the remaining the T-test of independent samples is used.  The results indicated that students positively perceived all the social studies traditions identified in the study at varying degree. The findings further established that, there is no significant difference between male and female students perception of the content of social studies education.  But there is a linear relationship between two students perceived the goals of the discipline and the extent of their implementation to promote effective citizenship it was thus, recommended among others the need for teachers to introduce students to the major traditions in social studies so as to enhance their perception of the subject. Keywords: Student, Perception, Social Studies, Education, Effective Citizenship